2012
DOI: 10.1111/j.1651-2227.2012.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐to‐skin care in neonatal intensive care units in the Nordic countries: a survey of attitudes and practices

Abstract: Skin-to-skin care is implemented in all Nordic neonatal units, but offered to various degrees, to various populations and to varying extents. Danish, Norwegian and Swedish units are offering SSC more extensively than units in Finland and Iceland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 30 publications
3
36
1
4
Order By: Relevance
“…Some units have family rooms where the family can stay with their infants for the entire hospital stay. Almost all units provide various degrees of kangaroo mother care and developmental care 27. The neonatal units have either their own milk bank or have access to a central breast milk bank for mother's own or donor breast milk.…”
Section: Methodsmentioning
confidence: 99%
“…Some units have family rooms where the family can stay with their infants for the entire hospital stay. Almost all units provide various degrees of kangaroo mother care and developmental care 27. The neonatal units have either their own milk bank or have access to a central breast milk bank for mother's own or donor breast milk.…”
Section: Methodsmentioning
confidence: 99%
“…In the last two decades, FCC based interventions have been developed to support the parent-child attachment relationship [6][7][8][9]. There is convincing evidence about the positive effects of Kangaroo Mother Care [9][10][11], but studies suggest there are huge differences in the provision of facilities to enable skinto-skin care and parental involvement [12,13]. A recent European survey, for example, found that 100% of included units in Sweden had reclining chairs near babies' cots and 100% had beds for the parents whilst in the UK these figures were 11% and 77% respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…IV-line has been reported as a barrier for SSC [21]. In addition, a shorter duration of parenteral nutrition can decrease infant pain, infections, and parental stress [22,23].…”
Section: Tablementioning
confidence: 99%